Decolonizing the Metropole: The Born-Translated Works of Najat El Hachmi and Agnès Agboton as Literary Activism - Anna C Tybinko (Studies in 20th & 21st Century Literature, 2022)
This article compares Agnès Agboton’s memoirs Más allá del mar de arena: Una mujer africana en España (‘Beyond the Sea of Sand: An African Woman in Spain,’ 2005) to Najat El Hachmi’s novel, La filla estrangera (‘The Foreign Daughter,’ 2015) to illustrate how these seemingly dissimilar works serve to make space for their author’s first languages in peninsular letters. Applying Rebecca Walkowitz’s conception of born-translated literature to the case of these Spanish and Catalan texts, it argues that the migratory tales of these two women writers constitute a contribution to the Global Hispanaphone. This rubric is typically conceived of as a decolonial framework that accounts for the diverse geographies, cultures, and languages formerly united under Spanish colonial rule. However, these two literary works are involved in a similar interrogation of the hegemony of Castilian Spanish via content, form, and, above all, self-translation.
Keywords: born-translated; Global Hispanophone; Castilian; Catalan; Gun; Tamazight; Najat El Hachmi; Agnès Agboton